2011
DOI: 10.1007/s11426-011-4434-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis of a cyclotide via intramolecular cyclization of peptide O-esters

Abstract: Cyclotides constitute a fascinating family of circular proteins containing ca. 30 amino acid residues. They have a unique cyclic cysteine knot topology and exhibit remarkable thermal, chemical and enzymatic stabilities. These characteristics enable them to have a range of biological activities and promising pharmaceutical and agricultural applications. Here, we present a practical strategy for the chemical synthesis of cyclotides through the intramolecular ligation of fully unprotected peptide O-esters. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…This is because loop 1 of MCoTI-II contains the natural trypsin inhibitory site, and it has proved tempting to modify residues in this loop to alter the enzyme inhibitory specificity from trypsin to pharmaceutically relevant proteases, including beta-tryptase for potential applications in inflammation [54]. All of the grafting studies have been underpinned by the development of approaches to make cyclotides using solid phase peptide synthesis [64][65][66][67][68][69][70][71][72] or by recombinant methods [12,58,[73][74][75][76]. Space limitations preclude a detailed discussion of the chemistry involved, but the field has been extensively reviewed [8,11,12,77,78] and can be summarized by noting that members of the Möbius and trypsin inhibitor subfamilies appear to be readily synthesizable, but members of the bracelet subfamily are, in general, very difficult to fold.…”
Section: Biological Activities and Pharmaceutical Applicationsmentioning
confidence: 99%
“…This is because loop 1 of MCoTI-II contains the natural trypsin inhibitory site, and it has proved tempting to modify residues in this loop to alter the enzyme inhibitory specificity from trypsin to pharmaceutically relevant proteases, including beta-tryptase for potential applications in inflammation [54]. All of the grafting studies have been underpinned by the development of approaches to make cyclotides using solid phase peptide synthesis [64][65][66][67][68][69][70][71][72] or by recombinant methods [12,58,[73][74][75][76]. Space limitations preclude a detailed discussion of the chemistry involved, but the field has been extensively reviewed [8,11,12,77,78] and can be summarized by noting that members of the Möbius and trypsin inhibitor subfamilies appear to be readily synthesizable, but members of the bracelet subfamily are, in general, very difficult to fold.…”
Section: Biological Activities and Pharmaceutical Applicationsmentioning
confidence: 99%
“…[6] The efficacy of this strategy has been shown by the convergent syntheses of several proteins consisting of up to six peptide segments. [7] Furthermore, several groups, [8,9] including ours, [10] developed ester or amide functionalities which can be converted into thioesters through an intramolecular acyl transfer (Scheme 1 c). In particular, the very recently developed approaches of the acyl transfer of secondary amides allow the synthesis of proteins by N-to-C assembly of multiple segments.…”
mentioning
confidence: 99%
“…Cyclotides are plant‐derived cyclic peptides, which show extensive biological activities, including antibacterial, anti‐HIV, and trypsin‐inhibitory activities . In 2012, Zheng et al (Figure A) successfully finished the chemical synthesis of cyclotide kalata B1 (KB1) through the intramolecular NCL of an unprotected peptide O ‐ester and subsequent oxidative refolding. In 2011, Macmillan et al found that a sequence‐specific N ‐to‐ S acyl shift could initiate the formation of C ‐terminal thioesters, which were key components for NCL.…”
Section: Strategies To Develop Cyclic Peptides Into Therapeutic Agentsmentioning
confidence: 99%